Septic Shock due to Acinetobacter Baumannii Infection with Complications of Acute Respiratory Distress Syndrome: A Case Report - Christina, Mikha; Noya, Fricilia; Freitas, Lurdes Acorta; Reis, Silvestre Dos; Priambodo, Ayu Prawesti; Mirwanti, Ristina (Indonesian Journal of Global Health Research, 2024)
Sepsis shock, characterized by sepsis-induced circulatory or metabolic disturbances, remains the leading cause of death in ICUs globally. Infection by Acinetobacter baumannii, which is frequently found in medical environments, can trigger life-threatening sepsis shock. This condition occurs when the bacteria or its bacterial products trigger adverse reactions from the immune system. ARDS, as a serious complication, results from endothelial damage that causes fluid to enter the alveoli, disrupting gas exchange and leading to respiratory failure. Purpose to describe a case in a patient diagnosed with epilepticus, with a history of autistic disorder, and non-specific pneumonia aged 30 years. This case report reviews a 30-year-old man admitted with a diagnosis of status epilepticus, with a history of autistic disorder, and non-specific pneumonia. The patient showed progressive improvement with initial therapy, including antiepileptic therapy and empirical antibiotics for pneumonia. However, the patient's condition deteriorated later, resulting in Acute Respiratory Distress Syndrome (ARDS) due to septic shock by Acinetobacter baumannii. The patient required mechanical ventilation and intensive management, including a change in antibiotic therapy and tracheostomy. With appropriate intervention, the patient showed improvement and was successfully discharged from mechanical ventilation. This patient with severe ARDS caused by sepsis shock due to Acinetobacter baumannii infection, demonstrates the importance of prompt and appropriate management of the complications of sepsis to prevent the patient's death. Acinetobacter baumannii infection causing ARDS and sepsis shock is a serious and rarely reported case, where aggressive treatment of sepsis with appropriate antibiotics and careful management of mechanical ventilation can improve the progression of ARDS.